A generalized chaotic encryption system for multimedia applications - R. Hasimoto-Beltrán (Revista Mexicana de Física, 2007)
Recently, several encryption schemes based on 1, 2, and 4 one-dimensional chaotic maps have been presented in the literature (see Ref. 1).The idea of increasing the number of maps is to provide more security and robustness to chaos-based cryptographic systems. In this paper,we propose a generalized encryption scheme based on N one-dimensional coupled chaotic maps, where only a window of m maps at a time(m · N) is active for the encryption process. The m-map window is randomly updated by shifting it circle-wise one map at a time throughthe entire N-map system. To add more security to the system, we randomly perturb the coupling parameter using current cyphertext output(spatiotemporal or global feedback); so that any change in the input data (plaintext) is reflected instantly in the total system (not only locally).Our generalized implementation is based on the scheme presented in Ref. 1, but it can also be implemented in any chaos based encryptionscheme. Our approach adds more robustness to the system, maintaining excellent statistical properties and fast performance for real-timemultimedia applications.